Experimental Study on the Conversion of Fuel Injection Motorcycles into Electric Vehicles Through Dynotest Performance Testing - Ari Aryadi; Reza Febriano Armas; Hamid Nasrullah; Anissa Shofia Zahra (Politeknik Piksi Ganesha Indonesia, 2024)
This study aims to test the results of converting a gasoline-fueled motorcycle with an injection system into an electric motorcycle in terms of horsepower and torque. The data from the unit conversion testing in this study used an experimental method with data analysis that compares the results of dyno tests on a gasoline-fueled motorcycle unit using variations of fuel octane values, with dyno test data from the unit after being converted into an electric vehicle. The testing equipment and materials used in the study were: Sportdyno 4.0, a 110 CC Injection Matic Motorcycle unit, and Pertamax Fuel. The results of this study show that the highest power and torque on the gasoline-powered motorcycle were 6.2 Horsepower (HP) at 6500 to 6600 rpm, and the highest torque was 6.8 N.m at 6400 rpm for the unit before conversion. After the conversion, the highest power achieved was 5.4 HP at an average of 2250 to 2500 rpm, and the highest torque was 28.48 N.m at 1100 rpm for the converted vehicle unit.Thus, it can be concluded from the average data analysis of the power and torque tests that the result of the electric vehicle conversion is 5.4 HP and 28.48 N.m.